2021
DOI: 10.14254/2071-789x.2021/14-3/13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cooperative & non-cooperative farmers in Kosovo

Abstract: As reported by the GDP per capita Kosovo is one of the poorest countries in Europe. Relying on the importance and dependence of Kosovo`s economy, it is evident that the development of agriculture sector is among the prime concern of the country`s strategy and international support programs. Several international studies assess the potential of agricultural cooperatives in transforming traditional agricultural farms to modern market-oriented business units, accelerating growth and addressing rural poverty. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Relatedly, a study by [26] in Mexico on what differentiate cooperative and non-cooperative smallholder farmers found that vertical integration specifically through cooperatives have statistical significant influence on farmers' offfarm income. Similarly, a study by [27] in Kosovo revealed that farmers engaged in vertically integrated market specifically cooperatives had higher income than non-members. Another study in Russia by [28] on the relationship between vertical integration and food security revealed that vertical integration for the meat and milk value chain results into higher performance of farmers in these subsectors.…”
Section: Empirical Literature Reviewmentioning
confidence: 96%
“…Relatedly, a study by [26] in Mexico on what differentiate cooperative and non-cooperative smallholder farmers found that vertical integration specifically through cooperatives have statistical significant influence on farmers' offfarm income. Similarly, a study by [27] in Kosovo revealed that farmers engaged in vertically integrated market specifically cooperatives had higher income than non-members. Another study in Russia by [28] on the relationship between vertical integration and food security revealed that vertical integration for the meat and milk value chain results into higher performance of farmers in these subsectors.…”
Section: Empirical Literature Reviewmentioning
confidence: 96%
“…5.8% of non-cooperative farms are headed by women, but cooperative farms have twice more women as managers, so overall the proportion of women is very low, but still relevant to the deviation in favour of cooperatives, where the proportion of women is almost double (11.1%) (Muriqi et al, 2021). Some research has explained this by the fact that, unlike men, women are more willing to cooperate with each 54/166 other, easier to send them to training courses, are more committed to the work, and pay more attention to agricultural production therefore they are better in the situations where high-level cooperation is needed (Muriqi et al, 2021). Also according to the KAS (Kosovo Agency for Statistics), women's participation in entrepreneurial activities is limited, which indirectly affects the number of women employed in the private sector (Ramadani et al, 2015a).…”
Section: The Role Of Social Cooperativesmentioning
confidence: 99%
“…Agriculture, a sector vital for many economies, has also witnessed the transformative potential of cooperative strategies. Muriqi, Baranyai, and Fekete-Farkas undertook a comparative analysis of cooperative and noncooperative farmers in Kosovo (Muriqi et al, 2021). Their study revealed significant differences between the two groups, with cooperative farmers displaying higher levels of agricultural education, greater family involvement in agricultural activities, and increased access to resources.…”
Section: Comparative Analysis Of Strategiesmentioning
confidence: 99%